MOTIVATION AND REASON IN SOCIAL INFORMATION INTERACTION (Revista Inclusiones, 2021)
In social philosophy, mass informatization has led to cases of manipulating people’s consciousness, which illustrate how irrational social information can shape motivation and reasons for individuals’ behavior. The article aims to analyze the information interaction in the public consciousness, when there is formed motivation and then reason for the behavior of an individual or social group. The analysis of motivating reasons was based on R. Wedgwood’s classification and the dialectical materialistic methodology, which allowed defining such basic concepts as reason, motivation, social information, rational, irrational, and relationship. The concepts underlay the study of social information interaction when motivation transitions into a specific reason for an individual’s action stage by stage. There was described the beginning, content, and end of this process characterized by the author’s view of comparing the subject of social information according to its properties as it relates to an individual’s social experience. Rational and irrational properties of social information are considered to determine the reason for an individual’s behavior in the information space of public consciousness. The research findings contribute to mitigating cases of manipulating people’s consciousness and maintaining the effective social management.